MEMBANGUN PELAYANAN PUBLIK YANG PRIMA : STRATEGI MANAJEMEN HUMAS DALAM PENYAMPAIAN PROGRAM UNGGULAN DI LEMBAGA PENDIDIKAN - qoimah qoimah (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2018)
The presence of educational institutions as an alternative choice for students.their scientific repertoire is felt quite useful. To further enhance the role and participation. non-formal education institutions in the community then the existence of a public relations figure required. Roles and duties of public relations here to represent the existence and image of educational institutions in addition to addressing all forms of problems related to public relations. The problem that arises is the role and function of a public relations practitioner is perceived not enough role and important then not many educational institutions that set up a separate department for the public relations department. The existence of this public relations should be at the top level of management so that it can provide input at the institutional management level. The concepts used in relation to this writing are related to the functions and roles of Public Relations, Public Relations management strategies and communication strategies of educational institutions. To get a good image is required a good management strategy, one of which is to improve the relationship with the parties that establish cooperation with educational institutions in this case represented by a public relations. Given the importance of role and function public relations then it is appropriate that its presence is also considered in educational institutions.